Дослідження можливостей енергозбереження у технології виробництва залізобетону - Шульгін, Юрій Віталійович; Жнітов, Я. В. (НТУ "ХПІ", 2015)
Теплові установки застосовуються для тепловологістної обробки бетонних виробів. Тепловологістна обробка здійснюється в теплових установках різної конструкції, але із застосуванням різних видів теплоенергоносіїв. У зв’язку з цим є актуальним виявлення раціонального теплоенергоносія з точки зору мінімальної собівартості тепловологістної обробки. Представлена авторами стаття є дослідженням ефективності енергоносіїв, які застосовуються в теплових установках для теплової обробки залізобетонних виробів.

The industry of the construction materials is characterized by an ample amount of thermal treatment processes that produce a significant influence on the quality and cost price of the products manufactured by the company. However, the most efficient method of speeding-up the concrete hardening process remains today the thermal treatment, which allows the concrete to reach the required strength within few hours. Thermal treatment is carried out using different heat carriers, including water steam, the combustion gases and ambient air mixture, electric heating, electrical curing, etc. The scientific paper presented by the authors is devoted to the studies of the efficiency of electric carriers used by thermal plants for the thermal treatment of concrete products. Theoretical and calculated investigations carried out by the authors allowed them to establish that the efficient energy carrier for the thermal treatment of reinforced concrete products is presently considered to be the electric energy.
Studying the opportunities of the energy saving using reinforced concrete production technology FlowVision
Keywords: залізобетонні вироби; теплова обробка; теплоенергоносії; енергоефективність; thermal treatment; energy carriers; flow rate; concrete; power efficiency